AN EMPIRICAL ANALYSIS OF THE IMPACT OF ECONOMIC AND NON-ECONOMIC FACTORS OF CAPITAL FLIGHT: AN EXAMPLE OF THE ECONOMETRIC MODEL - E. I. Markovskaya; A. V. Belov (Финансы: теория и практика)
Article Retracted.The paper presents the results of a study related to the assessment of the impact of economic and non-economic factors on the international export of capital.The purpose of the study was an econometric assessment of the influence of some economic and non-economic indices on the export of capital in 2015 throughconstruction of a consistent econometric model.To select a method for the capital outflow evaluation for the research purposes, three potential methods for measuring the scale of the capital escape from the country are analyzed: the CBR method, the World Bank method and assessment of direct foreign investments. The authors exposed methodological differences in approaches to evaluating the amount of capital outflow to be taken into account in such studies.In the course of the study a number of regression models were developed and some of them confirmed the existence of the relationship between capital outflow and non-economic factors.It is concluded that the non-economic factors influence the magnitude of capital outflow from the national economy and political events may significantly affect the decisions of investors. In our models, non-economic factors such as presidential and parliamentary elections, time to start a business have an impact on the amount of capital outflow. The study is a part of the research work related to the development of the matrix of the Russian economy investment climate. [1] Subsequent research activities may include the construction of a model to analyze the influence of economic and non-economic factors on the capital outflow amount in different types of national economies (for example, in developed and developing countries). This will make it possible to use simulation results to predict amounts of the capital outflow from the Russian economy.The research findings can be used in the practice of the development of the economic and investment policies at the macro and the micro levels, the national economylevel as well as at the regional level